Geography of antimony in Roman and early medieval colorless glass - Sainsbury, V (Corning Museum of Glass, 2017)
This note, provided as an interim and summary report on research made possible by the Rakow Grant for Glass Research, is an indication of what can be achieved from the synthesis of a large amount of geographically recorded glass data. Specifically, it focuses on changing patterns in antimony in colorless glass in Britain between the third and fourth centuries. The assumption is that antimony falls out of use in the third century, and this can be used to track Britain’s access to fresh glass and the glass trade.